2001
DOI: 10.2746/042516401776254763
|View full text |Cite
|
Sign up to set email alerts
|

Equine dysautonomia (grass sickness) is associated with altered plasma amino acid levels and depletion of plasma sulphur amino acids

Abstract: Summary To determine whether equine dysautonomia (ED) is associated with alterations in plasma amino acid metabolism, plasma amino acid profiles were determined for horses with acute (n = 10), subacute (n = 6) and chronic (n = 7) ED and for healthy cograzing horses (n = 6) and control horses (n = 10). Horses with acute ED had perturbations in plasma amino acid profiles resembling those of severe protein malnutrition. In addition, horses with ED and cograzing healthy horses had depletion of the plasma sulphur a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 48 publications
3
28
0
Order By: Relevance
“…The low concentrations of methionine noted in FD and in-contact cats is consistent the depletion of methionine and cyst(e)ine reported in EGS and healthy in-contact horses [9]. In the present study it was unfortunately not possible to meaningful assess the cats’ cyst(e)ine status because the low plasma/serum cyst(e)ine concentrations noted in all cats were likely artefactual, due to cysteine interaction with sulphydryl groups on plasma proteins and subsequent loss when the protein was precipitated during sample preparation.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The low concentrations of methionine noted in FD and in-contact cats is consistent the depletion of methionine and cyst(e)ine reported in EGS and healthy in-contact horses [9]. In the present study it was unfortunately not possible to meaningful assess the cats’ cyst(e)ine status because the low plasma/serum cyst(e)ine concentrations noted in all cats were likely artefactual, due to cysteine interaction with sulphydryl groups on plasma proteins and subsequent loss when the protein was precipitated during sample preparation.…”
Section: Discussionsupporting
confidence: 81%
“…The increase in essential amino acids in FD may reflect increased tissue protein catabolism in response to reduced food intake. In contrast, horses with EGS had reduced plasma concentrations of many essential amino acids, consistent with severe protein malnutrition, and increased concentrations of some non-essential amino acids [9]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A few years ago, a study on plasma amino acid profiles of EGS horses found that these were similar to those occurring in subacute/chronic cyanide toxicity (McGorum and Kirk 2001). Furthermore, horses grazing EGS pastures had higher blood cyanide, and plasma and urinary thiocyanate concentrations, which is consistent with an increased exposure to cyanogens (McGorum and Anderson 2002).…”
mentioning
confidence: 92%